Generalization of Multipulse Transmission Techniques for Ultrasound Imaging. (October 2015) - Lin, Fanglue; Cachard, Christian; Varray, François; Basset, Olivier
To increase the contrast-to-tissue ratio (CTR) in contrast imaging or the signal-to-noise ratio (SNR) in tissue harmonic imaging, many multipulse transmission techniques have been suggested. This article first recalls the various imaging techniques proposed in the literature and then presents a mathematical background to synthesize and generalize most of the multipulse ultrasound imaging techniques. The formulation presented can be used to predict the relative amplitude of the nonlinear components in each frequency band and to design new transmission sequences to either increase or decrease specified nonlinear components in each harmonic band. Simulation results on several multipulse techniques agree with the results from previous studies.